A new species and a new record of the amphipod genus Cymadusa Savigny, 1816 (Senticaudata, Ampithoidae) from India - Thacker, Dimple; Myers, Alan; Trivedi, Jigneshkumar (Zootaxa, 2023)
The present study recorded Cymadusa filosa Savigny 1816 for the first time from India along with the description of a new species Cymadusa kaureshi n. sp. The newly described species C. kaureshi n. sp. can be differentiated from its closely related congeners C. setosa (Haswell, 1879) and C. tattersalli Peart, 2004 in having 3 articulated accessory flagellum of antenna 1 and male gnathopod 2 palm with small proximal knob-like process. The record of Cymadusa filosa Savigny, 1816 by Rabindranath (1972) from Tamil Nadu does not match with the description and illustrations of C. filosa sensu stricto in having mid palmar tooth on male gnathopod 2; antenna 1 with 3 articulated accessory flagellum and gnathopod 1 significantly longer and slender than gnathopod 2. Since the record of Rabindranath (1972) significantly differs from C. filosa sensu stricto, we assume that the Tamil Nadu specimen could be an undescribed species. Moreover, all the previous reports from India of C. filosa are erroneous, and here in this study we report the first confirmed record of C. filosa from India.